Exploiting members of the BAHD acyltransferase family to synthesize multiple hydroxycinnamate and benzoate conjugates in yeast. Issue 1 (December 2016) - Eudes, Aymerick; Mouille, Maxence; Robinson, David; Benites, Veronica; Wang, George; Roux, Lucien; Tsai, Yi-Lin; Baidoo, Edward; Chiu, Tsan-Yu; Heazlewood, Joshua; Scheller, Henrik; Mukhopadhyay, Aindrila; et al.
Abstract Background BAHD acyltransferases, named after the first four biochemically characterized enzymes of the group, are plant-specific enzymes that catalyze the transfer of coenzyme A-activated donors onto various acceptor molecules. They are responsible for the synthesis in plants of a myriad of secondary metabolites, some of which are beneficial for humans either as therapeutics or as specialty chemicals such as flavors and fragrances. The production of pharmaceutical, nutraceutical and commodity chemicals using engineered microbes is an alternative, green route to energy-intensive chemical syntheses that consume petroleum-based precursors. However, identification of appropriate enzymes and validation of their functional expression in heterologous hosts is a prerequisite for the design and implementation of metabolic pathways in microbes for the synthesis of such target chemicals. Results For the synthesis of valuable metabolites in the yeastSaccharomyces cerevisiae, we selected BAHD acyltransferases based on their preferred donor and acceptor substrates. In particular, BAHDs that use hydroxycinnamoyl-CoAs and/or benzoyl-CoA as donors were targeted because a large number of molecules beneficial to humans belong to this family of hydroxycinnamate and benzoate conjugates. The selected BAHD coding sequences were synthesized and cloned individually on a vector containing the Arabidopsis geneAt4CL5, which encodes a promiscuous 4-coumarate:CoA ligase active on hydroxycinnamates and benzoates. The variousS. cerevisiae strains obtained for co-expression of At4CL5 with the different BAHDs effectively produced a wide array of valuable hydroxycinnamate and benzoate conjugates upon addition of adequate combinations of donors and acceptor molecules. In particular, we report here for the first time the production in yeast of rosmarinic acid and its derivatives, quinate hydroxycinnamate esters such as chlorogenic acid, and glycerol hydroxycinnamate esters. Similarly, we achieved for the first time the microbial production of polyamine hydroxycinnamate amides; monolignol, malate and fatty alcohol hydroxycinnamate esters; tropane alkaloids; and benzoate/caffeate alcohol esters. In some instances, the additional expression ofFlavobacterium johnsoniae tyrosine ammonia-lyase (FjTAL) allowed the synthesis ofp -coumarate conjugates and eliminated the need to supplement the culture media with 4-hydroxycinnamate. Conclusion We demonstrate in this study the effectiveness of expressing members of the plant BAHD acyltransferase family in yeast for the synthesis of numerous valuable hydroxycinnamate and benzoate conjugates.